Selection of Reference Genes for RT-qPCR Analysis Under Intrinsic Conditions in the Hawthorn Spider Mite, Amphitetranychus viennensis (Acarina: Tetranychidae) - Yang, Jing; Gao, Yue; Liu, Zhongfang; Lu, Junjiao; Zhang, Yuying; Zhang, Pengjiu; Fan, Jianbin; Zhou, Xuguo; Fan, Renjun (Frontiers in Physiology, 2019)
Hawthorn spider mite, Amphitetranychus viennensis Zacher, is one of the most devastating sap-sucking pest of deciduous fruit trees. Most recently, we sequenced the genome of A. viennensis. To take advantage of the newly established genomic resources, however, we need to develop a standardized protocol for Real-Time Quantitative Reverse Transcription PCR (RT-qPCR), one of the most effective and broadly adopted methods to quantify gene expression. Following the MIQE (Minimum Information for publication of Quantitative real time PCR Experiments) guidelines, internal references are required to counter the innate technical errors and biases in RT-qPCR analysis. Based on previous knowledge, we hypothesized that internal references for RT-qPCR analysis reside in housekeeping genes. To examine this hypothesis, we assessed the stability of nine housekeeping genes from A. viennensis transcriptome. These candidates, including 18S ribosomal RNA(18S), 28S ribosomal RNA (28S), Elongation factor 1-alpha (EF1A), Actin3, V-ATP vacuolar-type H+-ATPase (V-ATPase), α-tubulin (α-tubulin), Ribosomal protein L13 (RPL13), 40S ribosomal protein S9 (RPS9), and Glyceraldehyde 3-phosphate dehydrogenase (GAPDH), have been used extensively as the reference genes for RT-qPCR analysis. The expression of these candidates under intrinsic conditions, across developmental stage, sex, and diapause, was evaluated by a panel of computational programs, including geNorm, Normfinder, BestKeeper, and ΔCt method. Finally, a specific set of reference genes is recommended for each intrinsic conditions, respectively, based on RefFinder, a comprehensive analytical platform integrating all four above-mentioned algorisms. Overall, V-ATPase, Actin3, and GAPDH are consistently stably expressed across all the intrinsic conditions in A. viennensis. In addition, we compared reference genes recommended for different developmental stages among the nine sap-sucking arthropods, including four spider mites, A. viennensis, Tetranychus urticae, Tetranychus cinnabarinus, and Panonychus citri, and five hemipterans, Myzus persicae, Aphis gossypii, Toxoptera citricida, Lipaphis erysimi, and Sogatella furcifera. Not surprisingly, rRNAs and ribosomal proteins, the most abundant RNA species, is the top choice for the reference gene(s), and follows by EF1A, Actin, GAPDH, and tubulin, which all exceed 10% chance of been selected. Information present here lays the foundation for the genomic and functional genomic research in sap-sucking arthropods in general and A. viennensis in particular.